Level of awareness regarding MIS-C among medical students and surgeons in Switzerland - Raphael Vuille-dit-Bille; Laura Guglielmetti; Stefan Holland-Cunz; Sebastiano Brazzola; Stephanie Gros; Julian Louis Muff (World Journal of Pediatric Surgery)
Background Multisystem inflammatory syndrome in children (MIS-C) is a disease that emerged during the COVID-19 pandemic. Patients exhibit symptoms mimicking the clinical presentation of an acute abdomen, representing a novel differential diagnosis, particularly in the young generation. This study aims to investigate the current level of awareness of MIS-C among surgeons and medical students.Methods We conducted an anonymous online questionnaire among members of the Swiss Surgical Society and Swiss medical students. The questionnaires collected participants’ baseline demographics and their awareness regarding MIS-C.Results Both students and surgeons obtained very low scores in the self-assessment and had a low score in the section with awareness questions (true score). In medical students, we observed a positive correlation between self-assessment and true scores (ρ=0.422, p=0.001), while surgeons had a negative correlation (ρ=-0.243, p<0.001). Furthermore, there was a positive correlation between gender and self-assessment (ρ=0.245, p<0.001), depicting a higher self-assessed score in female surgeons (median female self-assesment=5, IQR: 2-7). Likewise, board-certified pediatric surgeons and surgeons treating both children and adults had a higher self-assessment compared with non-pediatric surgeons. In both populations (surgeons and students), the true scores were similar in all the variables analyzed. Two-thirds of surgeons stated that MIS-C should be considered a differential diagnosis, and about half of surgeons indicated MIS-C being part of their differential diagnosis already.Conclusion The results show an insufficient level of awareness concerning MIS-C among students and surgeons, warranting implementation in students’ curriculum and surgeons’ continuous training.